LAPAROSCOPIC VERSUS OPEN APPENDICECTOMY IN ADULTS - Sharma, Ravi Kumar; Karan, Rosy (Student’s Journal of Health Research Africa, 2024)
BACKGROUND One of the most popular techniques is appendectomy. Though it is still debatable, laparoscopic appendectomy (LA) is thought to be the initial course of treatment for complex appendicitis. This study examines mean operating time, surgical site infection, and duration of hospital stay to compare open and laparoscopic appendectomy procedures for individuals with perforated appendices. MATERIALS AND METHODS This randomized research was performed at the Department of General Surgery, KIMS, Bhubaneshwar from 2022-23. A total of 100 individuals were enrolled in the research, with 50 people in both groups. Analysis was done on outcome metrics such as blood loss, length of hospital stays before oral intake, mean operating time and postoperative problems. RESULTS The mean operating time was significantly longer for LA (101.46 ± 44.4 minutes) compared to OA (84.4 ± 43.1 minutes; p = 0.008). However, LA showed a lower incidence of wound infections (2%) compared to OA (8%), though this difference was not statistically significant (p = 0.09). LA patients experienced a significantly shorter hospital stay (10.54 ± 5.57 days) compared to OA patients (13.19 ± 8.4 days; p = 0.015). CONCLUSION The laparoscopic procedure for appendectomy is an effective and efficient surgical procedure with marginally increased hospital expenses. The laparoscopic procedure has clinically advantageous benefits over the open method, including a reduced rate of wound infection, early food tolerance, a shorter stay in the hospital, and less need for postoperative analgesics. RECOMMENDATIONS LA is recommended over OA for perforated appendices due to its advantages, such as fewer wound infections and shorter hospital stays, despite longer operating times. Further research with larger randomized trials is needed to confirm these findings and evaluate the cost-effectiveness of LA.